Omphalocele and macroglossia: a case of Beckwith-Wiedemann syndrome - Mahmood, Shafqat; Alam, Muhammad Tanveer (International Journal of Research in Medical Sciences, 2023)
Beckwith-Wiedemann syndrome (BWS) is a pediatric overgrowth disorder which predisposes to tumor development. The following case study examined a prenatal finding of omphalocele with postnatal findings of macroglossia and cutaneous hemangioma, ultimately leading to a diagnosis of BWS. This case highlighted the features of BWS, the diagnostic principles and the importance of a multidisciplinary team approach to its management.